Faktualisasi Kehidupan Umat Islam yang Belum Damai - Aulia Rosa Nasution (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
The life of Muslims today is faced by a variety of challenges that exist both from within and from outside. Muslims are faced with various problems that threaten from the environment (internal) and from the external environment (external) which is very influential for the lives of Muslims. This research is intended to examine the problems in the lives of Muslims that arise as challenges in the future. The religion of Islam revealed by Allah S.W.T serves as a guide and guide for humanity as a whole to be able to be applied in daily life, both in the form of values, attitudes and behavior as well as rules to create a peaceful world and avoid conflict. Even so, in daily facts, Muslims continue to intersect with political and social conflicts as a challenge for an increasingly modern world civilization that demands Muslims to be able to face it according to Islamic guidance as a religion that teaches peace and harmony for all humanity in both global and global contexts. local.